An In Vitro Engineered Osteochondral Model as Tool to Study Osteoarthritis Environment. Issue 2 (27th October 2022) - Scalzone, Annachiara; Cerqueni, Giorgia; Wang, Xiao‐Nong; Ferreira‐Duarte, Ana; Dalgarno, Kenny; Mattioli‐Belmonte, Monica; Gentile, Piergiorgio
Abstract: Osteoarthritis (OA) is a joint degenerative pathology characterized by mechanical and inflammatory damages affecting synovium, articular cartilage (AC), and subchondral bone (SB). Several in vitro, in vivo, and ex vivo models are developed to study OA, but to date the identification of specific pharmacological targets seems to be hindered by the lack of models with predictive capabilities. This study reports the development of a biomimetic in vitro model of AC and SB interface. Gellan gum methacrylated and chondroitin sulfate/dopamine hydrogels are used for the AC portion, whereas polylactic acid functionalized with gelatin and nanohydroxyapatite for the SB. The physiological behavior of immortalized stem cells (Y201s) and Y201s differentiated in chondrocytes (Y201‐Cs), respectively, for the SB and AC, is demonstrated over 21 days of culture in vitro in healthy and pathological conditions, whilst modeling the onset of cytokines‐induced OA. The key metrics are: lower glycosaminoglycans production and increased calcification given by a higher Collagen X content, in the AC deep layer; higher expression of pro‐angiogenic factor ( vegf ) and decreased expression of osteogenic markers ( coll1, spp1, runx2 ) in the SB. This novel approach provides a new tool for studying the development and progression of OA. Abstract : Design and manufacturing of a highly reproducible, easy‐to‐manipulate, and low‐cost 3D in vitro osteochondral model mimicking the interface between the deep layer of articular cartilage and subchondral bone, with the aim of studying the main features of cells in these two compartments during osteoarthritis onset, compared to healthy conditions.